Analisis Run-Off Sebagai Dampak Perubahan Lahan Sekitar Pembangunan Underpass Simpang Patal Palembang dengan Memanfaatkan Teknik GIS - Riani Muharomah (Jurnal Teknik Sipil dan Lingkungan, 2014)
The amount of surface run off is influenced by land use, soil type, and slope.  To analyze the impact of the changes in land use on the runoff ,  it is needed to know the amount of coverage or the area to be analyzed, elevation plans, and soil conditions. The elevation changes in an area can cause the changes of catchment area on it. So that, the runoff and the direction that occur also changes. The purpose of this study is to analyze the change and amount of runoff  around Underpass Simpang Patal Palembang by using GIS method, and to analyze the capacity of drainage plan on Underpass Simpang patal. The method that is used in this study using Geographic Information System (GIS) method, that is DEM analysis to catchment area changes, land use data overlay, and to analyze the amount of runoff from the area plan rainfall. This study used the existing elevation data (spotheight data), rainfall data of  Palembang in the past 10 years, the height plan data of Underpass Simpang Patal, and land use data from Peta Garis Kota Palembang with the scale 1:1000. The analysis of the results showed that the elevation change in Underpass Simpang Patal construction site cause the catchment area around that location is changed. The smallest percentage of land change to the runoff that will occur is 0.159%, and the biggest percentage of land change to the runoff that will occur is 90.022%. The analysis of the drainage plan capacity of Underpass Simpang Patal Palembang show that the drainage plan is able to accept the runoff predictions that will happen, but it’s not economic. The economic dimention is 45 cm x 90 cm.   Keywords : runoff, catchment area, Geographic Information System (GIS), and elevation